Temperature Adaptation in a Changing Climate - Storey, Kenneth B (CABI, 2014)
All living organisms on Earth are slaves to environmental temperature change. Temperature rules the fundamental bio- chemistry of cellular metabolism - temperature change alters the rates of all metabolic reactions and changes the conformations of all macromolecules. Temperature also constrains the lives of most organisms - for example, temperature change affects all aquatic organisms by altering the solubility of oxygen in water, tissue freezing at temperatures below 0°C is lethal to the vast majority of organisms, and sustained high temperatures above about 50°C are also lethal to most. Organisms can use biochemical, physiological or behavioural adaptations to help them cope with temperature variation, within limits, and these have been explored in depth by hundreds of researchers (Hochachka and Somero, 1984; Willmer et al., 2005; Rao et al., 2006). Most organisms on Earth are ectotherms, having limited or no control over their temperature. We humans are `luckier' than most in being among the small percentage of species on Earth that are endotherms, having internal control over body temperature.